Loss‐of‐function mutation of the calcium sensor CBL1 increases aluminum sensitivity in Arabidopsis. Issue 2 (2nd February 2017) - Ligaba‐Osena, Ayalew; Fei, Zhangjun; Liu, Jiping; Xu, Yimin; Shaff, Jon; Lee, Sung‐Chul; Luan, Sheng; Kudla, Jörg; Kochian, Leon; Piñeros, Miguel
Summary: Despite the physiological importance of aluminum (Al) phytotoxicity for plants, it remained unknown if, and how, calcineurin B‐like calcium sensors (CBLs) and CBL‐interacting protein kinases (CIPKs) are involved in Al resistance. We performed a comparative physiological and whole transcriptome investigation of an Arabidopsis CBL1 mutant ( cbl1 ) and the wild‐type (WT). cbl1 plants exudated less Al‐chelating malate, accumulated more Al, and displayed a severe root growth reduction in response to Al. Genes involved in metabolism, transport, cell wall modification, transcription and oxidative stress were differentially regulated between the two lines, under both control and Al stress treatments. Exposure to Al resulted in up‐regulation of a large set of genes only in WT and not cbl1 shoots, while a different set of genes were down‐regulated in cbl1 but not in WT roots. These differences allowed us, for the first time, to define a calcium‐regulated/dependent transcriptomic network for Al stress responses. Our analyses reveal not only the fundamental role of CBL1 in the adjustment of central transcriptomic networks involved in maintaining adequate physiological homeostasis processes, but also that a high shoot–root dynamics is required for the proper deployment of Al resistance responses in the root.